2005
DOI: 10.1074/mcp.m500040-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Mass Analysis Using Labeled Lysines (DIMAL-K)

Abstract: Here we describe an original strategy for unbiased quantification of protein expression called difference in mass analysis using labeled lysine (K) (DIMAL-K). DIMAL-K is based on the differential predigestion labeling of lysine residues in complex protein mixtures. The method is relevant for proteomic analysis by two-dimensional electrophoresis and MALDI-TOF mass spectrometry. Protein labeling on lysine residues uses two closely related chemical reagents, S-methyl thioacetimidate and S-methyl thiopropionimidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…These soluble proteins may play important roles in the progression of inflammatory diseases. Secretomic analysis of glia has been previously used to determine the secreted protein profiles during inflammatory responses [3,4,6,51,65,66,81]. In this study, we found that PAI-1 is one of the major proteins released by mixed glial cultures after inflammatory stimulation, and we provide evidence that PAI-1 is able to regulate microglial activation, migration, and phagocytosis under inflammatory condition .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These soluble proteins may play important roles in the progression of inflammatory diseases. Secretomic analysis of glia has been previously used to determine the secreted protein profiles during inflammatory responses [3,4,6,51,65,66,81]. In this study, we found that PAI-1 is one of the major proteins released by mixed glial cultures after inflammatory stimulation, and we provide evidence that PAI-1 is able to regulate microglial activation, migration, and phagocytosis under inflammatory condition .…”
Section: Discussionsupporting
confidence: 57%
“…A large-scale analysis of glia-derived proteins may broaden the understanding of glial functions in the CNS [3,6,51]. We and others have previously investigated the secretome of brain glial cells [3,4,6,7,51,65,66]. Proteins secreted from glial cells have been shown to regulate neuron–glia communication and to play important roles in interglial interactions [67].…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that GFAP, despite being a cytoskeletal protein, is normally secreted from astrocytes, as has been found to occur for vimentin from macrophages (Mor-Vaknin et al, 2003). Studies of the astrocyte secretome have largely utilized cell cultures and are complicated by the problem of correcting for contamination by cytoplasmic contents – most reports finding that vimentin and not GFAP is secreted (Delcourt et al, 2005; Keene et al, 2009; Greco et al, 2010). Dowell et al (2009) did find GFAP in the supernatant from cultured mouse astrocytes, but considered it a contaminant.…”
Section: Discussionmentioning
confidence: 99%
“…However, Urushitani et al (17) found that mutant SOD1, once secreted in association with chromogranins, is deleterious because it induces microgliosis and death of motor neurons in co-cultures. High-throughput technologies have started to identify the factors released by the astrocytes, aiming to uncover their various functions and the toxic molecules released (2022). Numerous proteins have been listed, but the link with pathological events is still missing.…”
Section: Introductionmentioning
confidence: 99%